A new, post-Lee Kuan Yew era - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2011)
Eugene Tan, asst prof of law at SMU writes a commentary on Minister mentor Lee Kuan Yew's departure and how it reinforces the belief that the Singapore systems is based on institutions, not personalities.